ONParkinson – Innovative mHealth to support the triad: patient, carer and health professional - Madeira, Rui Neves (2016)
Trabalho apresentado no 6th EAI International Symposium on Pervasive Computing Paradigms for Mental Health, 28-30 novembro 2016, Barcelona, Espanha